Analisis citra merek, kualitas produk, dan bauran promosi terhadap keputusan pembelian pasta gigi Pepsodent (Studi kasus di perumahan Ciledug Indah 2 periode Maret-Mei 2015) - Loekman, Priscilla; Chairy, Chairy (Universitas Tarumanagara, 2017)
Increased business development in toothpaste, all businesses strive to attract customers and retain customers in various ways. Pepsodent toothpaste always strives to provide a brand image such as quality superior to other brands. Pepsodent toothpaste is a quality product that organizes dental health events and optimizes the promotion mix always informing new products. The purpose of this research is an analysis of brand image analysis, product quality, and promotion mix of its effect on to purchase decision of Pepsodent toothpaste. This research is done by literature study, observation, interview, and spreading of the questionnaire. This population is the competitor users of Pepsodent Toothpaste in Ciledug Indah Estate 2. The sample used is 67 people selected using probability sampling, precisely using simple random sampling. Simple correlation analysis tool to know the relationship between variables. Multiple linear regression analysis is useful to know the effect of the dependent variable. Variables of brand image and quality partially have a significant influence on the public interest in using Pepsodent toothpaste. The promotional mix variable partially has no significant effect on the public interest in using Pepsodent toothpaste. The regression equation formed is Y = 3.548 + 0.26 (X1) + 0.497 (X2). Brand image variable (X1) has a positive effect on purchasing decisions. Product quality variables (X2) also have a positive effect on purchasing decisions. Brand image variables and product quality simultaneously have a significant influence on the public interest in using Pepsodent toothpaste.